Respiratory Failure Associated with Ascariasis in a Patient with Immunodeficiency - Lanocha Aleksandra; Zdziarska Barbara; Lanocha-Arendarczyk Natalia; Kosik-Bogacka Danuta; Guzicka-Kazimierczak Renata; Marzec-Lewenstein Ewa (Case Reports in Infectious Diseases)
In industrialized countries, risk groups for parasitic diseases include travelers, recent immigrants, and patients with immunodeficiency following chemotherapy and radiotherapy and AIDS. A 66-year-old Polish male was admitted in December 2012 to the Department of Haematology in a fairly good general condition. On the basis of cytological, cytochemical, immunophenotypic, and cytogenetic analysis of bone marrow, the patient was diagnosed with acute myeloblastic leukemia. On the 7th day of hospitalization in the Department of Haematology, patient was moved to the Intensive Care Unit (ICU) due to acute respiratory and circulatory failure. In March 2013, 3 months after the onset of respiratory failures, a mature form of Ascaris spp. appeared in the patient’s mouth. This report highlights the importance of considering an Ascaris infection in patients with low immunity presenting no eosinophilia but pulmonary failure in the central countries of Europe.